The current state of evaluator education: A situation analysis and call to action. (August 2019) - Gullickson, Amy M.; King, Jean A.; LaVelle, John M.; Clinton, Janet M.
Highlights: Evaluator education is critical to evaluation's emergence as a profession. A CIPP analysis of evaluator education highlighted key gaps and issues in every area. Further efforts are required to advance evaluator education and evaluate its quality. Research questions to shape this work are provided. Abstract: Education is critically important for the maintenance and growth of programme evaluation and its emergence as a profession. This position paper presents evaluator education as an initiative and provides a foundation for its evaluation. In it, the authors use Stufflebeam's Context, Input, Process, and Product (CIPP) model to frame a review of the literature and practice. We follow this analysis of the current state of evaluator education in formal settings, with discussion of its implications, and directions for future research and action. Our analysis suggests that there is much work to be done to understand the needs for evaluator education, to delineate standards for quality in both education and practice, to identify the inputs and processes most effective for addressing those needs, and to document its ultimate impacts. The paper provides a call to action for improving the quality, consistency, and integrity of this important work.